Participating in development : approaches to indigenous knowledge - Sillitoe, Paul, 1949-; Bicker, Alan; Pottier, Johan (A.S.A. monographs ;, 2002)
This thought- provoking and challenging collection focuses on how anthropologists can define and use indigenous knowledge without compromising anthropological expectations.